PENGARUH LITERASI KEUANGAN SYARIAH DAN KEPERCAYAAN NASABAH TERHADAP BRAND EQUITY PADA BANK SYARIAH INDONESIA (BSI) CABANG BONE - Rasni, Yuliana; Zulkifli, Zulkifli; Hasni, Hasni (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study aims to determine the extent to which Islamic financial literacy and customer trust influence brand equity at Bank Syariah Indonesia. The research was conducted with 110 respondents using a quantitative approach. Data analysis was carried out using the Partial Least Squares (PLS) method. The results of the study indicate that Islamic financial literacy and customer trust have a significant effect on brand equity, both partially and simultaneously. These findings suggest that enhancing Islamic financial literacy and strengthening customer trust are important strategies in building the brand strength of Bank Syariah.